E-COMMERCE DEVELOPMENT PROSPECTS IN THE ENTERPRENEURSHIP OF THE RUSSIAN FEDERATION - Suglobov, Aleksandr; Repushevskaya, Olga; Tkach, Aleksandr; Dashkov, Leonid; Balalova, Elena (Revista Inclusiones, 2020)
At the current stage of development of market relations, the goal of enhancing the innovative component in the business of an enterprise for performance improvement is extremely important. The emergence of global computer networks has marked the rise of a new communications environment and a market with a large number of prospective high-income customers